دراسة تأثير بارامترات الجدار الخازن للحرارة (Trombe-wall, TW) على حمل التدفئة في الأبنية - جورج, رامي; وسوف, حسن; برباره, غـيث سـمير (Latakia University Journal -Engineering Sciences Series, 2016)
البحث عبارة عن دراسة نظرية برمجية لتأثير بارامترات الجدار الخازن للحرارة ((Trombe wall في تخفيض أحمال التدفئة والذي يؤدي بدوره إلى ترشيد استهلاك الطاقة التقليدية وتحسين الشعور بالراحة الحرارية للقاطنين في البناء، وذلك باستخدام برنامج المحاكاة TRNSYS عند الشروط المناخية لمدينة طرطوس. أظهر البحث أنه مع زيادة الإيصالية الحرارية للجدار الخازن للحرارة، ينخفض حمل التدفئة الكلي. والقيمة المثلى لها هي حيث نحصل على زيادة في نسبة الوفر في حمل التدفئة مقدارها مقارنة في حالة . أيضاً وجـدنا أن القيمة المثلى للسـعة الحـرارية النوعية للجـدار هي حيث نحصل على زيادة في نسبة الوفر مقدارها مقارنة مع حالة . كما أظهر البحث أن السماكة المثلى للفراغ الهوائي بين الجدار والزجاج هي ، حيث مع زيادة السماكة عن هذه القيمة، يصبح مقدار الزيادة في نسبة الوفر أقل من . وأن أفضل اتجاه للجدار الخازن للحرارة هو باتجاه الجنوب، حيث نحصل على أكبر نسبة وفر في حمل التدفئة مقدارها وتتناقص مع دوران البناء باتجاه الشمال حيث نحصل على أقل نسبة وفر ومقدارها . أظهر البحث أيضاً أن استخدام الجدار الخازن للحرارة أدى إلى ارتفاع في درجة الحرارة الداخلية للبناء خلال أشهر الشتاء واقترابها من درجة حرارة الارتياح الحراري للقاطنين في البناء، وكان أكبر ارتفاع في درجة الحرارة الداخلية في يوم 12 من كانون الثاني ومقداره 6.8 [ºC]. The research aims to achieve theoretical programming study of the influence of the parameters of the thermal storage wall (Trombe wall) in minimizing heating loads which in turn leads to reduce the consumption of conventional energy and to improve heat comfort of building inhabitant by using the simulation program TRNSYS at climatic conditions of Tartous city. The investigation showed that by increasing the conductivity of thermal storage wall, the total heating load decreases. It’s optimum value is λ=1.11[W/mK] where we obtain an increasing in heating load rate equals5.63[%] comparing with the state when λ=0.28[W/mK]. Also, we found that the optimum value specific capacitance of the wall is Cp=2000[kJ/kgK] where we obtain an increasing in saving rate equals 3.03[%] comparing with the state when Cp=1000[kJ/kgK]. The investigation showed that the optimum thickness of air spacing between wall and glazing is 0.2[m]. Whereas any increasing of thickness to become larger that optimum value, the increasing of saving rate be less than 0.5[%].In addition, the investigation showed that the best location of thermal storage wall is toward the south where we obtain the greatest saving rate of heating load equals 54.5[%], which decreases with the building rotation toward the north where we obtain the least saving rate equals 17.7[%]. The investigation showed that the using of thermal storage wall causes rising building internal temperature during winter months, this leads to bring it near the temperature of heat comfort of building inhabitants. The largest rising of internal temperature was in 12 January which equaled 6.8[ºC].